Synthesis of new photo-cured phosphorus-containing oligoestermethacrylates with a spacer in the structure - B. A. Buravov; A. Al-Khamzawi; E. S. Bochkarev; N. Kh. Grichishkina; S. V. Borisov; N. V. Sidorenko; O. I. Tuzhikov; O. O. Tuzhikov (Тонкие химические технологии, 2022)
Objectives. To synthesize phosphorus-containing oligoestermethacrylates spatially separated by spacers of aliphatic or aromatic structure and evaluate their effect on photocuring kinetics.Methods. For determining the qualitative and quantitative composition of the synthesized compounds, the following methods were used: thin layer chromatography; chromatographic and mass spectrometry; infrared spectroscopy; 1H, 13C, 31P nuclear magnetic resonance spectroscopy; differential scanning calorimetry. The dielectric loss tangent was determined on a specially designed optical cell with an ultraviolet (UV) light source to an immittance meter. Elemental analysis was performed on an energy dispersive X-ray fluorescence spectrometer.Results. Spatially separated oligoestermethacrylates based on phosphorus trichloride containing aliphatic or aromatic spacers in the structure were synthesized. During the interaction of glycidyl methacrylate with phosphorus trichloride in the mass of the latter, reaction products were shown to be formed both according to the Krasusky rule from the side of the α-carbon atom, as well as against this rule with the formation of isomeric products. Obtaining these compounds in bulk is possible only in the presence of a homopolymerization inhibitor. The influence of the spacer structure on the curing rate of oligoestermethacrylates under the action of UV radiation has been established. It has been shown that the introduction of a spacer into the oligomer structure is accompanied by an increase in the induction period by a factor of 39 compared to a sample without a spacer.Conclusions. The results obtained indicate the possibility of obtaining new oligoestermethacrylates with aliphatic and aromatic spacers in the structure. The influence of the structure of the spacer on the kinetics of photocuring is determined.